Incidence, characteristics and risk factors of hypofibrinogenemia associated with tigecycline: A multicenter retrospective study in China - Leng, Bing; Shen, Chengwu; Gao, Tiantian; Zhao, Kai; Zhao, Xuemei; Guo, Yujin; Wu, Jiyong; Yang, Jing; Fang, Wei; Zhang, Jicheng; Zhang, Yahui; Sun, Chao; et al. (Frontiers in Pharmacology, 2022)
Background: Tigecycline was recently found to cause coagulation disorders, especially hypofibrinogenemia, which may interfere with the administration of antimicrobial therapy. This study aimed to investigate the incidence and clinical characteristics of and risk factors for tigecycline-associated hypofibrinogenemia. Methods: In this multicenter retrospective study, patients receiving tigecycline or imipenem–cilastatin to treat Gram-negative bacterial infections in nine Chinese tertiary hospitals between January 2020 and December 2020 were enrolled. Baseline data and coagulation variables were compared using cohort and case–control studies. Results: Totals of 485 patients treated with tigecycline and 490 patients treated with imipenem–cilastatin were included in this study. Compared with imipenem–cilastatin, tigecycline was associated with reduced fibrinogen and prolonged activated partial thromboplastin time and prothrombin time (all p<0.001), with the most remarkable change in fibrinogen (down by 48.0%). The incidence of hypofibrinogenemia in patients treated with tigecycline was >50%, with propensity score-matched analysis or not. The relative risk of hypofibrinogenemia with tigecycline versus imipenem–cilastatin was 2.947 (95% CI: 2.151-4.039) at baseline balance. Tigecycline-associated hypofibrinogenemia led to a higher incidence (12.1%) of bleeding events. However, none of supplemental therapies after withdrawal had an effect on the normalization of fibrinogen levels. The risk factors for tigecycline-associated hypofibrinogenemia were treatment duration ≥6 days (odds ratio [OR] 5.214, 95% confidence interval [CI] 2.957-9.191, p<0.001), baseline fibrinogen <4 g/L (OR 4.625, 95% CI 2.911-7.346, p<0.001), cumulative dose ≥1000 mg (OR 2.637, 95% CI 1.439-4.832, p=0.002), receiving CRRT (OR 2.436, 95% CI 1.179-5.031, p=0.016), baseline PT >14 s (OR 2.110, 95% CI 1.317-3.380, p=0.002) and baseline total bilirubin >21 μmol/L (OR 1.867, 95% CI 1.107-3.147, p=0.019), while the protective factor was skin and soft tissue infection (OR 0.110, 95% CI 0.026–0.473, p=0.003). Conclusion: The clinical characteristics of and risk factors for tigecycline-associated hypofibrinogenemia identified in this study can offer practical reference for the clinical management of patients.